"Four-component" assembly of polyaromatic 4H-cyclopenta[b]thiophene structures based on GaCl3-promoted reaction of styrylmalonates with 5-phenylthiophene-2-carbaldehyde. Issue 10 (7th March 2019) - Borisov, Denis D.; Chermashentsev, Grigory R.; Novikov, Roman A.; Tomilov, Yury V.
Graphical abstract: Highlights: A new reaction of styrylmalonates with aromatic aldehydes has been developed. This process is four-component and promoted by GaCl3 . The process represents assembly of polyaromatic thiophene structures. It involves two [2 + 3]-annulation steps and para -substitution into Ph-ring. Resulting structures have a strong absorption in a near UV spectral region. Abstract: New "four-component" self-assembly of polyaromatic thiophene structures based on styrylmalonates and 5-phenylthiophene-2-carbaldehyde has been developed. This process is promoted by GaCl3 and involves two [2 + 3]-annulation steps on the CHO-groups and para -substitution into one Ph-ring. The main feature of discovered process is a high diastereoselectivity with a significant increase in molecular complexity. The resulting polyaromatic structures containing two thiophene moieties in each structure have intense color and strong absorption in a near UV spectral region with absorption maxima in the range of 257–360 nm.